BPIFA1 is a secreted biomarker of differentiating human airway epithelium - Clifton, Clarissa; Niemeyer, Brian F.; Novak, Richard; Can, Uryan Isik; Hainline, Kelly; Benam, Kambez H. (Frontiers in Cellular and Infection Microbiology, 2022)
In vitro culture and differentiation of human-derived airway basal cells under air-liquid interface (ALI) into a pseudostratified mucociliated mucosal barrier has proven to be a powerful preclinical tool to study pathophysiology of respiratory epithelium. As such, identifying differentiation stage-specific biomarkers can help investigators better characterize, standardize, and validate populations of regenerating epithelial cells prior to experimentation. Here, we applied longitudinal transcriptomic analysis and observed that the pattern and the magnitude of OMG, KRT14, STC1, BPIFA1, PLA2G7, TXNIP, S100A7 expression create a unique biosignature that robustly indicates the stage of epithelial cell differentiation. We then validated our findings by quantitative hemi-nested real-time PCR from in vitro cultures sourced from multiple donors. In addition, we demonstrated that at protein-level secretion of BPIFA1 accurately reflects the gene expression profile, with very low quantities present at the time of ALI induction but escalating levels were detectable as the epithelial cells terminally differentiated. Moreover, we observed that increase in BPIFA1 secretion closely correlates with emergence of secretory cells and an anti-inflammatory phenotype as airway epithelial cells undergo mucociliary differentiation under air-liquid interface in vitro.